Industrial relations: the contribution of the universities - McCarthy, Charles (Statistical and Social Inquiry Society of Ireland, 1980)
Although I have spent most of my life in the practice, one way or the other, of industrial relations, my responsibilities now lie within a university and it seems to me that one must consider what a university can contribute in this area. In the very short period of twenty minutes, all I can do is sketch some thoughts for you. The fact that our session tonight consists of a number of brief and necessarily undeveloped views is an indication perhaps that this ancient society recognises that* there is a public preoccupation about industrial relations but does not really believe that it is the subject of serious academic study. My view ? naturally I suppose ? is that it is indeed a matter of serious academic study and that such a study would make at least some contribution to meeting what has been described as the challenge of the times ? although I am not without some anxiety that the ancient society may be correct and I may be mistaken
Symposium on Necessary Changes in Industrial Relations
Read before the Society, 13 December 1979
Keywords: Universities; Academic discipline of industrial relations; Human resource management; Industrial Relations; 314.15